Correlations Between Physical Activity, Smoking Habit And Attitude In Elderly With Incidence of Osteoporosis - Kiki Familia Dimyati (Universitas Airlangga, 2017)
Osteoporosis is a degenerative disease that mostly affects elderly people. There are several risk factors for osteoporosis, two of which are physical activity and smoking habits. This study aims to analyze the effect of physical activity, smoking habits, and attitudes of the elderly on the incidence of osteoporosis. This research is an observational study with a case-control study design. The number of samples in this study was 66 elderly who visited the osteoporosis clinic of the Husada Utama Specialist Hospital in Surabaya in August - December 2015. A systematic random method was chosen as a way to determine the study sample. The independent variables in this study are physical activity, smoking habits, and attitudes, while the dependent variable is osteoporosis. Data analysis using a logistic regression test. The results showed that physical activity (p = 0.003; OR = 6.824; 95% CI = 1,958–23,782), smoking habits (p = 0.047; OR = 3,121; 95% CI = 1,133–8,603), and attitude (p = 0.026 ; OR = 3,538; 95% CI = 1,277 - 9,805) affect the incidence of osteoporosis. The conclusion of this study is that physical activity is the most influential risk factor for the incidence of osteoporosis after controlled smoking and elderly attitudes, so it is advisable to do physical activity at least 3 times a week, consume food or drinks with balanced nutrition, adequate rest, and avoid stressors and stop smoking.